AN ANNOTATED TRANSLATION OF SLOW AND STEADY PARENTING BY CATHERINE A. SANDERSON - Nurfatimah, Eva (Journal of Language and Literature, 2017)
This is an annotated translation research. The researcher herself translated the text and, at the same time, writes a commentary on her own process. The purposes of this research are: (1) to attain factual information concerning the problems encountered of researcher during the process of translation of the source language into target language, and (2) to present plausible solutions to the problems encountered by the researcher during the process of translation. The method used in conducting this annotated translation research are introspective and retrospective methods. The result of the analysis revealed that not all items of the principles of translation and not all of those strategies of translation were used for analysis. From the six items in the principle of translation, there are five items which used for analysis. Those are meaning, idiom, form, source language influence, and style and clarity. Of the 30 items in the translation strategies, the researcher/ translator used 12 items to help researcher/ translator translates the text. Those are literal translation, loan, transposition, unit shift, clause structure change, sentence structure change, cohesion device, synonymy, paraphrase, cultural filtering, explicitness, and interpersonal change. Keywords: Translation, Annotated, Parenting